Serum parameters as prognostic biomarkers in a real world cancer patient population treated with anti PD-1/PD-L1 therapy. (31st December 2022) - Minichsdorfer, Christoph; Gleiss, Andreas; Aretin, Marie-Bernadette; Schmidinger, Manuela; Fuereder, Thorsten
Abstract: Background: Immune checkpoint inhibitors (ICI) are regarded as a standard of care in multiple malignancies. We hypothesized that serum parameters are of prognostic value in ICI treated patients suffering from solid tumours. Methods: Data from 114 patients treated with ICIs for solid malignancies from 2015 to 2019 at the Medical University of Vienna were collected retrospectively. Data included baseline characteristics, cancer type, serum parameters such as lactate dehydrogenase (LDH), C-reactive protein (CRP), albumin (Alb) and lymphocyte counts as well as overall survival (OS) and progression free survival. Additionally, the Gustave Roussy Immune Score (GRIm score) and the Glasgow prognostic score (GPS) were calculated. Cox regression models including time-dependent effects and strata for tumour type were used. Prognostic factors were pre-selected using a relaxed LASSO approach. Results: The majority of patients were male (64.9%). The most common cancer types were non-small cell lung cancer (30.7%) and renal cell carcinoma (21.9%). Increased LDH and CRP were associated with poor 6-month OS (Hazard ratios (HR)=1.16 and 1.06 per 20% LDH/CRP increase; 95% CI 1.07–1.26 and 95% CI 1.03–1.09, respectively; p < .001). Both GRIm Score and GPS had a significant influence on OS (GRIm: HR = 2.84, 95% CI 1.72–4.69; p < .001 for high vs. low; GPS HR 3.57, 95% CI 1.76–7.25; p < .001 for poor vs. good). The proportion of explained variation (PEV) of our full multivariable model was significantly higher compared to the GRIm and GPS (PEV = 29.5% vs. 14.8% and 14.65%). When grouped into quartiles according to the individual 8-weeks change, both increased LDH and CRP correlated with poor OS (LDH ( p =.001) and CRP ( p < .001)). Conclusion: The results of this analysis suggest that serum parameters might have prognostic value for the outcome of cancer patients treated with ICI, regardless of the tumour type. Key messages: In this retrospective analysis, 114 patients with solid tumours were included. The results of this analysis point out that pre-treatment LDH, CRP and albumin levels are strongly prognostic for a poor 6-month OS. In addition to that, a high GRIm-score and poor GPS were associated with a worse OS (GRIm: HR = 2.84, 95% CI 1.72–4.69; p < .001 for high vs. low; GPS HR = 3.57, 95% CI 1.76–7.25; p < .001 for poor vs. good). Pre-treatment serum parameters might have prognostic value for the outcome of cancer patients treated with ICI, regardless of the tumour type.